Особливості теплообміну витих теплообмінників при зовнішньому обтіканні - Туз, Валерій Омелянович; Лебедь, Наталія Леонідівна; Литвиненко, Максим Петрович (Національний технічний університет "Харківський політехнічний інститут", 2021)
Представлені результати дослідження процесу конвективного теплообміну при зовнішньому обтіканні розташованої в кільцевому каналі трубної поверхні витого теплообмінника. Визначені фактори, які мають найбільший вплив на інтенсивність процесу, а саме: геометричні характеристики поверхні теплообміну і параметри теплоносія. Аналіз отриманих результатів свідчить про нелінійну залежність інтенсивності теплообміну по довжині теплообмінника. У результаті узагальнення експериментальних даних отримана залежність для визначення довжини теплової початкової ділянки.

Perfecting the existing technologies and developing new ones require to rethink the processes in order to obtain qualitatively new results. Widespread use of cryogenic engineering in the chemical industry and medicine calls for a thorough analysis of both the efficiency of thermodynamic cycles and the hardware design of appropriate equipment. The power necessary to obtain low working medium temperatures is distributed between the cooling of the object and the losses in the various elements of the cryogenic setup. One of the best ways to increase the efficiency of the setup is to use the cold energy recovery. This is done by using various designs of recuperative heat exchangers, such as twisted heat exchangers. Existing methods of calculating the parameters of power equipment are based on empirical dependencies, which require some justification and clarification in order to be used for calculating cryogenic equipment parameters. The article describes the experimental setup, presents the research methods applied and analyses the results of the study on convective heat transfer in external flow past the tubular surface of the twisted heat exchanger. The obtained results for the laminar gas flow mode at Re < 2300 allowed determining the length of the initial heat section depending on the regime parameters of the contact phases and the geometric specifications of the twisted heat exchanger. The obtained dependence will make it possible to refine the method of calculating the parameters of the twisted heat exchanger in the annular channel.
Particularity of heat exchange of twisted heat exchangers in external flow
Keywords: витий теплообмінник; теплообмін при зовнішньому обтіканні; конвективний теплообмін у кільцевих каналах; конвективный теплообмен в кольцевых каналах; twisted heat exchanger; convective heat transfer in external flow; convective heat transfer in annular channels